The Effect of Dexamethasone on Side Effects after Coronary Revascularization Procedures - M Abbaszadeh; Z Hosainkhan; A Soliemani; A Rabbani; R Shareafean (Tehran University of Medical Sciences, 2007)
Introduction: Corticosteroids decrease side effects after noncardiac elective surgery. The aim of this study was to determine the prophylactic effects of IV dexamethasone (6mg×2) in preventing side effects after cardiac surgery. Methods and Materials: In a randomized, double blinded, placebo-controlled study 184 ASA physical status I or Il patients ranging 40-82 undergoing coronary revascularization surgery were enrolled in Imam Khomeini Hospital, medial sciences university of Tehran.Dexamethasone (6mg/mL) or saline (1mL) was administered after the just before surgery and a second dose of the same study drug was given on the morning after surgery.  The patients were assessed at 24 and 48h intervals after surgery as well as at the time of hospital discharge, to determine the incidence and severity of postoperative side effects. Results: Dexamethasone significantly reduced the incidences of nausea (P=0.034) and vomiting on the first postoperative day (P=0.005). In addition, dexamethasone significantly improves appetite on the first postoperative day (P=0.005). The corticosteroid decreased the incidences of atrial fibrillation AF (P=0.018) in the postoperative period. However, the corticosteroid failed to decrease the incidences postoperative pain. Conclusion: dexamethasone (12 mg in divided doses) is suggested in reducing nausea and vomiting, decreases of atrial fibrillation and improving appetite after cardiac surgery.